Vaccination in Rheumatology: New Data (Based on Recommendations of the European League Against Rheumatism) - B. S. Belov; G. M. Tarasova; N. V. Muravyova (Антибиотики и Химиотерапия, 2020)
Comorbid infections have a significant effect on morbidity and mortality in modern rheumatology, especially in immune-mediated inflammatory rheumatic diseases (IMIRD). In this regard, vaccination is becoming increasingly important in the prevention of infections in IMIRD. The article analyzes an updated version of the recommendations for vaccination of adult patients with IMIRD, proposed by experts of the European League Against Rheumatism at the end of 2019. The safety and immunogenicity of vaccination associated with the prevention of various infections in patients with IMIRD are discussed. The main directions of future research on this issue are outlined.